Technology, Its Application And Productivity Optimisation in Ghana: A Case Study - Tuzie, Christopher (2014)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Science degree in Industrial Mathematics